Oxford Handbooks Online 2016
DOI: 10.1093/oxfordhb/9780199739134.013.23
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative/Therapeutic Assessment

Abstract: The Collaborative/Therapeutic Assessment (C/TA) paradigm represents a significant shift from the traditional aims and techniques of psychological assessment. C/TA deliberately employs a variety of evidence-based techniques intended to maximize the potential that the process of assessment will result in meaningful therapeutic benefits for clients. The empirical support for the effectiveness of the C/TA approach is promising and demonstrates direct intervention effects on such indicators as self-esteem and sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In a recent chapter by Aschieri et al (2016), the authors summarized the evidence for TA and highlighted essential skills and techniques for facilitating successful, impactful psychological assessment. These skills were not unique to the TA approach but could apply to a variety of assessment-related situations and contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent chapter by Aschieri et al (2016), the authors summarized the evidence for TA and highlighted essential skills and techniques for facilitating successful, impactful psychological assessment. These skills were not unique to the TA approach but could apply to a variety of assessment-related situations and contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has failed to show better outcomes when comparing evidence‐based parenting programs as usual with programs enhanced with CF (Kazdin et al ., 2018). Other research in the area of therapeutic assessment (TA) has shown that enhancing diagnostic assessments through the use of a collaborative, supportive approach to assessment can improve engagement, follow‐through and outcomes (Aschieri, Fantini & Smith, 2016). Positive outcomes have been associated with use of TA with parents of youth with conduct problems (Smith, Handler & Nash, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…or "Why don't I feel like I have control over my life and my future? "; Smith & George, 2012), in order to orient the testing phase and develop an individualized assessment intervention session, followed by an interactive summary and discussion session (Aschieri et al, 2016). Accordingly, assessment is client focused rather than test focused (Finn, 2020;Finn & Tonsager, 1997).…”
Section: Assessment As Treatmentmentioning
confidence: 99%